2020
DOI: 10.3390/ijerph17207408
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism, Related Factors and Oral Health-Related Quality of Life Among Vietnamese Medical Students

Abstract: Although bruxism is a common issue with a high prevalence, there has been a lack of epidemiological data about bruxism in Vietnam. This cross-sectional study aimed to determine the prevalence and associated factors of bruxism and its impact on oral health-related quality of life among Vietnamese medical students. Bruxism was assessed by the Bruxism Assessment Questionnaire. Temporomandibular disorders were clinically examined followed by the Diagnostic Criteria for Temporomandibular Disorders Axis I. Perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
8
0
6
Order By: Relevance
“…As we know that higher frequency of parafunctions tended to be associated with more severe stress and impaired QoL at the beginning of the study, we can say that those variables obviously play a larger role in patients with more frequent parafunctional activities and are positively affected by the therapy. The association of oral parafunctional activities with stress and quality of life has been established in a number of studies 39‐41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know that higher frequency of parafunctions tended to be associated with more severe stress and impaired QoL at the beginning of the study, we can say that those variables obviously play a larger role in patients with more frequent parafunctional activities and are positively affected by the therapy. The association of oral parafunctional activities with stress and quality of life has been established in a number of studies 39‐41 …”
Section: Discussionmentioning
confidence: 99%
“…The association of oral parafunctional activities with stress and quality of life has been established in a number of studies. [39][40][41] The within-subject analysis showed that the QoL of the HFP patients increased after 3 months, in contrast to the LFP group where significant improvement occurred only after the 6th month. Better QoL after 3 months, in the HFP group, is probably a consequence of education and attention to the role of clenching and various other harmful habits and prevention of nocturnal parafunctions and consequently less muscle pain and headaches.…”
Section: Ta B L E 3 Treatment Outcomes (Means and Ses) Depending On Frequency Of Oral Parafunctionsmentioning
confidence: 98%
“…En el presente estudio se observa que un 47.1% de la población exhibe probable bruxismo, lo que es similar a los resultados obtenidos por Ordoñez-Plaza et al, (18) con un 52%, aunque cabe señalar que este estudio solo incluyó el bruxismo de vigilia. Por su parte Phuong et al, (21) en su estudio donde se evalua el posible bruxismo, obtuvo un 51.2%. No obstante, dichas cifras no concordaron con el estudio de Silva A.…”
Section: Discussionunclassified
“…Por otra parte, siguiendo con el bruxismo, se observa que la manifestación circadiana más frecuente fue la de vigilia con 49%, mientras que la del sueño obtuvo un 9%. Este porcentaje es opuesto a lo identificado en la investigación de Phuong et al, (21) en la que el 38.2% es bruxismo de sueño y el 23.4% corresponde a la vigilia.…”
Section: Discussionunclassified
See 1 more Smart Citation